The Shared Transportation Industry in China: Examining the Influence of Regional Environmental Factors on New Venture Formation - Yan Zhou; Sangmoon Park; Justin Zuopeng Zhang; Xin Rong (Journal of Advanced Transportation)
China’s shared transportation industry is leading innovation, driving employment, and promoting regional economic growth. China’s aggressive efforts to promote the development of various transportation sectors motivate our investigation of this emerging industry. We examine the influence of regional environmental factors on new venture formation using a dataset encompassing newly established bike-sharing startups in 257 cities in China from 2015 to 2019. The empirical results show that entrepreneurial capital, entrepreneurial support policies, and urban auxiliary infrastructure positively impact the formation of new ventures. However, no significant relationship exists between industrial policy, competitive urban infrastructure, and new business formation. This study expands the scope of the existing research studying the characteristics of entrepreneurial space, offers inspiration for future startups entering the field of shared transportation in choosing entrepreneurial locations, and provides theoretical guidance for the government in formulating policies to attract entrepreneurial activities.